Temporal characteristics of the final delivery phase and its relation to tenpin bowling performance - Razman, R.; Wan Abas, Wan Abu Bakar; Abu Osman, Noor Azuan; Cheong, J.P.G. (2011)
Spatial and temporal variability in the execution of skills has been analyzed in many sports. An expert performer is commonly referred to as being more consistent in the execution of skills compared to a novice. The purpose of this study was to analyze temporal characteristics and variability of the final delivery phase and examine how it is related to bowling level and performance. Two level of bowlers were used in this study - 18 elite (Male=10, Female=8; Bave 213.2±6.80; BRvel 17.66±0.85mph) and 12 semi-elite bowlers (Male=7, Female=5; Bave 181.3±9.36; BRvel 16.90±1.46mph). The final delivery phase consisted of three major events which were the arm swing, front foot slide and ball release. The temporal variable that was measured was execution time and the between-trial temporal variability, while average bowling score and ball release velocity represented the performance criteria. In general, the results indicate that the temporal characteristic between the two groups were quite similar, but in terms of relationship to bowling performance, front foot slide time was correlated with bowling average. Variability wise, the elite group was less consistent in front foot slide execution time. There were no significant differences or correlations for the other variables. It was concluded that lower temporal variability was not indicative of higher playing level or better bowling performance. © 2011 Springer-Verlag.